The Sedative Effect of Propranolol on Critically Ill Patients: A Case Series - Shiotsuka, Junji; Steel, Andrew; Downar, James (Frontiers in Medicine, 2017)
Introduction Recent studies have examined the effectiveness of alpha-2-adrenergic agonists for controlling delirium and agitation. Propranolol, a non-selective beta-adrenergic antagonist with good penetration of the blood brain barrier, has not been investigated for this purpose. Material and Methods We retrospectively reviewed the medical records of all patients who were prescribed propranolol in our Medical-Surgical ICU from January 1, 2010 to December 31, 2013. We recorded the sedation level and daily dose of sedatives, analgesics, and antipsychotics administered each day for 6 days after starting propranolol, and compared them to the day before starting propranolol. Results Sixty-four patients met inclusion criteria. Thirty-eight episodes met exclusion criteria, leaving 27 patients (31 episodes). The administration of propranolol was associated with significant reductions in fentanyl equivalents (65%, P=0.009), midazolam equivalents (57%, p=0.048), propofol (16%, p=0.009), and haloperidol (44%, p=0.024) on Day 2 after starting propranolol compared with baseline. A stratified analysis showed that these decreases were seen regardless of clinical improvement or deterioration. Conclusion The use of propranolol was associated with a significant reduction in doses of sedatives and analgesia. Further studies are needed to determine whether propranolol may be a useful adjuvant for managing delirium and agitation in the ICU.